2015
DOI: 10.1371/journal.pone.0115438
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of a Soluble Dietary Fibre (Pectin) on Food Intake, Adiposity, Gut Hypertrophy and Gut Satiety Hormone Secretion in Rats

Abstract: Soluble fermentable dietary fibre elicits gut adaptations, increases satiety and potentially offers a natural sustainable means of body weight regulation. Here we aimed to quantify physiological responses to graded intakes of a specific dietary fibre (pectin) in an animal model. Four isocaloric semi-purified diets containing 0, 3.3%, 6.7% or 10% w/w apple pectin were offered ad libitum for 8 or 28 days to young adult male rats (n = 8/group). Measurements were made of voluntary food intake, body weight, initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 41 publications
7
65
1
1
Order By: Relevance
“…Pectin effects are mediated through its chemical-physiological properties as it passes through the gastrointestinal tract. It has been found that addition of pectin to the diet resulted in significantly higher weight and length of intestinal tissues and also in increasing small intestinal villus height and depth of the crypts in the small and large intestines compared with rats fed with a control diet (2,15,25). Data from other studies also indicate that consumption of diet with pectin leads to increased satiety, decreased food intake, body weight gain and total body fat in male rats (1,8,24).…”
Section: Introductionmentioning
confidence: 97%
“…Pectin effects are mediated through its chemical-physiological properties as it passes through the gastrointestinal tract. It has been found that addition of pectin to the diet resulted in significantly higher weight and length of intestinal tissues and also in increasing small intestinal villus height and depth of the crypts in the small and large intestines compared with rats fed with a control diet (2,15,25). Data from other studies also indicate that consumption of diet with pectin leads to increased satiety, decreased food intake, body weight gain and total body fat in male rats (1,8,24).…”
Section: Introductionmentioning
confidence: 97%
“…As such, a fiber-rich diet is also one that is processed and absorbed more slowly [5]. Several studies have suggested that increased satiety and reduced food intake can result from increases in dietary fiber which correlated with weight loss [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This material has a confirmed positive impact on cholesterol reduction. It also leads to increased water retention (up to 7-8 times its mass in some instances), causing a rapid increase in the satiety hormones GLP-1 and PYY in rodent models [8], commonly targeted in several medically prescribed diabetes control medications [13]. Diets high in fiber have led to reduced weight in controlled clinical trials [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the water-holding capacity and induced viscosity of soluble fibers. Adam et al (2015) showed that dietary fiber eliminated food intakes so, rats gained less body weight and required more food to gain a gram of body weight than their counterpart control fed rats.The differences were highly significant at p ≤ 0.05 between the control and the tested groups ( table 7). For serum cholesterol, it could be observed that including cholesterol in rat's diets led to increase the level of serum cholesterol ISSN: 2320-5407 Int.…”
mentioning
confidence: 99%